CHEMICAL COMPOSITION AND ANTIMICROBIAL POTENTIAL OF SELECTED MEDICINAL PLANTS - AHMED YACOUBA COULIBALY; ROKIAH HASHIM; SHAIDA FARIZA SULAIMAN; OTHMAN SULAIMAN; LILY ZUIN PING ANG (International Journal of Pharma and Bio Sciences, 2014)
Different extracts from five medicinal plants were investigated for their antibacterial and antifungal activities by agar diffusion and microdilution methods. The extracts selectively exhibited antibacterial effect and the most active was the aqueous-acetone extract of Euphorbia balsalmifera against the Gram-negative bacteria Escherichia coli, Klebsiella pneumonia and Pseudomonas aeruginosa with diameters of inhibition zones (d) exceeding 9mm and the minimal inhibitory concentrations less than 5mg/ml. This extract also displayed significant antifungal activity against brown rot Fomitopsis palustris and carbamic acid methyl ester was identified by gas chromatography/mass spectrometer as a main contributor to this antimicrobial activity. The aqueous-acetone extract of Sporobolus pyramidalis was significantly active against all the fungal strains (d≥9mm) with an exception on Pycnoporus sanguineus. Scoparia dulcis was the most active against both white rot and brown rot fungi (d≥14mm). The antifungal activities of these extracts were found to be comparable to those of the standard Glycyrrhizin Acid Dipotassium Salt, foreseeing their use as sources of fungistats.